2x-(3-x)=5+6x

Simple and best practice solution for 2x-(3-x)=5+6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-(3-x)=5+6x equation:


Simplifying
2x + -1(3 + -1x) = 5 + 6x
2x + (3 * -1 + -1x * -1) = 5 + 6x
2x + (-3 + 1x) = 5 + 6x

Reorder the terms:
-3 + 2x + 1x = 5 + 6x

Combine like terms: 2x + 1x = 3x
-3 + 3x = 5 + 6x

Solving
-3 + 3x = 5 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-3 + 3x + -6x = 5 + 6x + -6x

Combine like terms: 3x + -6x = -3x
-3 + -3x = 5 + 6x + -6x

Combine like terms: 6x + -6x = 0
-3 + -3x = 5 + 0
-3 + -3x = 5

Add '3' to each side of the equation.
-3 + 3 + -3x = 5 + 3

Combine like terms: -3 + 3 = 0
0 + -3x = 5 + 3
-3x = 5 + 3

Combine like terms: 5 + 3 = 8
-3x = 8

Divide each side by '-3'.
x = -2.666666667

Simplifying
x = -2.666666667

See similar equations:

| 2x^2=15-x | | 4x-(x+3)=15 | | 7=(-5-m)+4(6-m) | | -8+(-15)=(-15)+(-8) | | 15x=12(x-3) | | 5x+5+6x=5 | | -3m+4+5m=-6 | | 10x-9=-2x-69 | | 20x^3=50x | | 6(x-9)+x=7(x-9)+9 | | 3x+5=5(x-3) | | (2x+11y)(4x-9y)= | | 0=x^3-19x+18 | | 2x^2+15x=-7 | | 5(c+.80)+6=50 | | 2a+30=4a-4 | | 20+57x-9x^2=0 | | 7(2x-3)=7 | | 2x^2+30x+8=0 | | -4(2x-1)=6(x-2)-2 | | 8(3x+2)-18=-68 | | 7f+5=10(f-7)-3f | | 35-5(2x-3)=20 | | 8x-3x-5+3.2x= | | 5y^2=45 | | 6-3x=2x-24 | | 9y^2-31y-20=0 | | 3a+50=104 | | 10x-3(4+5x)=44 | | x-(16)=44 | | -5x-1=-121+5x | | n+(n+2)+(n+4)=-30 |

Equations solver categories